Revision of the Mexican ladybird genus Vedalia Mulsant (Coleoptera: Coccinellidae) - Czerwiński, Tomasz; Szawaryn, Karol (Zootaxa, 2024)
The ladybird genus Vedalia was established by Mulsant in 1850 to accommodate a single species Vedalia sieboldii Mulsant. Since its description the genus attracted little attention, and its systematic position in modern classification of the subfamily Coccinellinae remained unclear. Here we provide revisionary study based on the type and non-type material from various collections. Male and female genitalia are illustrated for the first time, scanning electron microscopy (SEM) illustrations of the key characters are also provided. Position of the genus within the tribe Chnoodini Mulsant is confirmed. Distribution and biology of Vedalia are also discussed.